2004
DOI: 10.1002/pola.20190
|View full text |Cite
|
Sign up to set email alerts
|

Organic and polymer chemistry of electrophilic tri‐ and tetrasubstituted ethylenes

Abstract: A survey of the spontaneous reactions of electrophilic olefins and nucleophilic olefins is presented as an area in which organic chemistry merges with polymer chemistry. The products include both small molecules and polymers, arising via tetramethylene biradical zwitterions that can cyclize or initiate polymerizations. Electrophilic tri-and tetrasubstituted olefins are particularly useful in delineating the transition from radical chemistry to ionic chemistry. A periodic table embodying these results enables p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(52 citation statements)
references
References 100 publications
0
52
0
Order By: Relevance
“…Diethylamino ring-substituted BCPP were used in preparation of photorefractive composites (6,7). It was shown that electrophilic tri-and tetrasubstituted olefins are particularly useful in delineating the transition from radical chemistry to ionic chemistry (8). Previous studies showed that TSE containing substituents larger than fluorine have very low reactivity in radical homopolymerization due to polar and steric reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Diethylamino ring-substituted BCPP were used in preparation of photorefractive composites (6,7). It was shown that electrophilic tri-and tetrasubstituted olefins are particularly useful in delineating the transition from radical chemistry to ionic chemistry (8). Previous studies showed that TSE containing substituents larger than fluorine have very low reactivity in radical homopolymerization due to polar and steric reasons.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that electrophilic tri- and tetrasubstituted ethylenes are particularly useful in delineating the transition from radical chemistry to ionic chemistry [7]. In regards to polymerization reactivity, previous studies showed that TSE containing substituents larger than fluorine have very low reactivity in radical homopolymerization due to polar and steric reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction pathway is dependent on the disparity in the energy levels of the participating HOMOÀLUMO orbitals, and also on the reaction conditions [4]. A case in point (Scheme 1) is the reaction of p-methoxystyrene (1) with dimethyl cyanofumarate (2). When the reaction is performed at high concentration, the monomers form the alternating copolymer 3, and the kinetics of this free-radical co-polymerization was studied in great detail [5].…”
mentioning
confidence: 99%